(untitled) (Global Journal of Management and Business Research, 2012)
Financial statement fraud cases misled users such as investors and creditors. Therefore, the main objective of this study is to identify the association between five ratios of financial reporting risks to predict fraud. Consequently, this study also investigates the impacts of fraud detection on audit fee. Thus, sample of 10 of fraudulent companies and sample of 40 non fraudulent companies are being identified to achieve the objective. Stepwise logistic regression was being employed. The results clearly indicate that changes in sales, receivables and allowance for doubtful debts have significant effect of fraud detection. However, fraud detection gives no or little impact on audit fees.